Teori Produksi Berdasarkan Perspektif Islam - Habibulloh (Mabny: Journal of Sharia Management and Business, 2022)
Abstract Production activity is a mandatory thing to do in order to meet all human needs and to take advantage of the availability of natural resources to fulfill all what is needed by humans by producing them and processing them. In Islam itself, it is also explained about being a good producer based on the theory of production in Islamic economics. Therefore, this journal aims to provide a general description and knowledge of the general public and especially for producers to understand the flow of the Islamic religion in explaining production theory and regulating it. The method used to describe this research is descriptive qualitative method, meaning that the technique used in this research is a literature study that focuses on finding information from journals, books or other forms of writing. The results of this study are a producer in the view of Islam has limits in production, but this limitation does not only apply to creativity but also to the prohibition on producing illicit goods. Basically, conventional theory and sharia have differences in terms of the amount, revenue and costs themselves, in conventional production theory also recognizes the interest system which is contrary to sharia production theory which recognizes profit sharing.